Two Putative Cypovirus-Encoded miRNAs Co-regulate the Host Gene of GTP-Binding Nuclear Protein Ran and Facilitate Virus Replication - Lin, Su; Wang, Yongsheng; Zhao, Ze; Wu, Wanming; Su, Yun; Zhang, Zhendong; Shen, Manman; Wu, Ping; Qian, Heying; Guo, Xijie (Frontiers in Physiology, 2021)
miRNA plays important roles in regulating various biological processes, including host-pathogen interaction. Recent studies have demonstrated that virus-encoded miRNAs can manipulate host gene expression to ensure viral effective multiplication. Bombyx mori cypovirus (BmCPV), a double-stranded RNA virus with segmented genome, is one of the important pathogens for the economically important insect silkworm. Our present study indicated that two putative miRNAs encoded by BmCPV could promote the viral replication by inhibiting the gene expression of Bombyx mori GTP-binding nuclear protein Ran (BmRan), an essential component of the exportin-5-mediated nucleocytoplasmic transport of small RNAs. BmCPV-miR-1 and BmCPV-miR-3 are two of the BmCPV-encoded miRNAs identified in our previous studies. BmRan is a common target gene of them with binding sites all located in the 3′-untranslated region (3′-UTR) of its mRNA. The expression levels of the two miRNAs in the midgut of larvae infected with BmCPV gradually increased with the advance of infection, while the expression of the target gene BmRan decreased gradually. The miRNAs and the recombinant target gene consisting of reporter gene mCherry and 3′-UTR of BmRan mRNA were expressed in HEK293T cells for validating the interaction between the miRNAs and the target gene. qRT-PCR results revealed that BmCPV-miR-1 and BmCPV-miR-3 negatively regulate the target gene expression not only separately but also cooperatively by binding to the 3'-UTR of BmRan mRNA. By transfecting miRNA mimics into BmN cells and injecting the mimics into the body of silkworm larvae, it was indicated that both BmCPV-miR-1 and BmCPV-miR-3 could repress the expression of BmRan in BmN cells and in the silkworm, and the cooperative action of the two miRNAs could enhance the repression of BmRan expression. Furthermore, the repression of BmRan could facilitate the replication of BmCPV genomic RNAs. It is speculated that BmCPV-miR-1 and BmCPV-miR-3 might reduce the generation of host miRNAs by inhibiting expression of BmRan, thus create a favorable intracellular environment for virus replication. Our results are helpful for better understand of the pathogenic mechanism of BmCPV to the silkworm, and provide insights into one of the evasion strategies used by viruses to counter the host defense for their effective multiplication.